Halal food certification and business excellence: A conceptual paper / Zuhayr Khan Mustun - Mustun, Zuhayr Khan (Universiti Teknologi MARA, 2021)
The crux of this paper is to hypothesize that Halal food certification improves business excellence, by way of a conceptual framework highlighting the connectivity between both elements. There have been numerous studies focusing on Halal food certification and business excellence along different perspectives, yet there is a scarcity of research that explicitly studied both aspects together. As far as the methodological approach is concerned, analysis of various secondary sources related with the keywords and topic has been adopted. The paper takes the EFQM (European Foundation for Quality Management) model as the groundwork for discussion within the Halal food sector. Based on the literature review, it is propounded that Halal food certification can boost business excellence on the grounds of ethical leadership, holistic strategic thinking and planning, enhanced people management, fortified B2B partnership, effective logistics and supply chain management, and maximized accrued results (customer, people, society and business). The theoretical foundation of this study can support further in-depth research on both elements, and given its conceptual nature, the framework should be empirically tested.